Análise das variações do vibrato de cantoras líricas em duas cadências musicais de caráter alegre e triste - Priscila Oliveira Faria (2011)
This paper presents a description of possible patterns of vibrato applied to the characters sad and happy. Using spectral analysis and an algorithm of spectral analysis of tremor and vibrato of the human voice developed in the Graduate Program in Electrical Engineering and Physical of UFMG, it aims the recognition of spectral analysis as a tool that enables differentiation of emotional characters involved in the performance of opera singers. Themethodology included the recording of 10 opera singers, performing two cadenzas, one of sad character and the other of happy character. Each cadenza was performed on the vowel [a] with an interjection, featuring an attack on the note (F4) with a duration of 4 seconds, after which the singer went down and closed it. The data were analyzed with the GRAM 5.7 software and algorithm analysis of tremor and vibrato, considering the variables: rate, extent, regularity and waveform in order to verify the general trends in each studied character. The conclusion was that the vibrato for the characters happy and sad present values of rate and extent acceptable according to the literature. The value of the rate for the character happy was not the greater than that for the character sad as expected. The regularity was prevalent in most singers studied. As for the waveform, the sinusoidal aspect predominated in both characters studied and three of the studied singers presented irregularities in the implementation of vibrato for the character sad. Concerning the attack and the termination of vibrato for the character happy, 60% (6) of the singers had a curve of the vibrato with an attack and a termination with an ascending form in performance, whereas, for the character sad, the curve begins and ends with a descending form for 40% (4) of the participants of the study. The general trends that distinguish one character from the other in this study is that the vibrato attack occurs for the character happy with an ascending form and descending form for the character sad.